SWOT ANALYSIS FOR DEVELOPING THE CITRA NIAGA AREA TO IMPROVE THE COMPETITIVENESS OF EAST KALIMANTAN SOUVENIR BUSINESSES - Syafira Rahmalia Indah; Annisa Wahyuni Arsyad; Ummi Nadroh; Ahmad Firman Hakim (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
This study examines the development strategy of the Citra Niaga area to enhance the competitiveness of East Kalimantan’s souvenir business actors. The urgency of this research arises from the significant decline of Citra Niaga since 1980s and the challenges faced in the post-pandemic sales era, despite revitalization efforts by the government that have yet to yield optimal results for local entrepreneurs. The main theoretical framework used is the SWOT analysis (Strengths, Weaknesses, Opportunities, Threats), aimed at identifying and mapping the strategic position of the area. A descriptive qualitative research method was employed to gather in-depth data through interviews with souvenir business actors and relevant government agencies (The Ministty of Public Works and Public Housing), questionnaires for SWOT factor weighting and rating, and documentation review. Purposive sampling was applied with the criterion of business actors having operated for a minimum of 10 years, to gain historical insight and rich experience. The SWOT analysis results place Citra Niaga in Quadrant I, indicating a strong internal position and significant external opportunities. The recommended main strategy is the Strength-Opportunity (SO) Strategy, which focuses on maximizing product innovation supported by human resource training and promoting the uniqueness and diversity of products with government backing. Recommendations include the utilization of e-commerce platforms and the implementation of government-supported innovation development and digital marketing programs for business actors.